Implikasi Penerapan Good Corporate Governance terhadap Kinerja Keuangan pada Perusahaan Perbankan - Nindia Salsha Noveka; Bara Zaretta; Agus Prayitno; Vicky Oktavia (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the influence of institutional ownership, managerial ownership, and independent commissioners as mechanisms of Good Corporate Governance on the financial performance (ROA) of banking companies in Indonesia. Using a quantitative approach with an associative method, secondary data were collected from 47 banking companies listed on the Indonesia Stock Exchange during the period 2019–2023. The analysis was conducted using descriptive statistics, classical assumption tests, and multiple linear regression with SPSS. The results show that institutional ownership and independent commissioners have a positive and significant effect on ROA, while managerial ownership has no significant effect. However, simultaneously, the three variables have a significant effect on Return on Assets (ROA). Future research is recommended to expand the scope of variables and consider other industry sectors in order to obtain more comprehensive insights into the impact of Good Corporate Governance mechanisms on financial performance.